2013
DOI: 10.3233/tad-130394
|View full text |Cite
|
Sign up to set email alerts
|

Deafblind people, stigma and the use of communication and mobility assistive devices

Abstract: This paper draws on interviews with 27 deafblind people and the mother of an autistic deafblind woman carried out as part of a larger research project on travel issues for blind, partially sighted and deafblind people to investigate and report on issues related to the use of communication and mobility assistive devices, in particular long canes, guide dogs, hearing aids and wheelchairs. The interviewees came from six different countries and both similarities and differences were found between the experiences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 61 publications
6
58
0
Order By: Relevance
“…However, older participants who had frequently used the cane revealed only positive experiences. The ambivalence concerning the cane has previously been reported by Ellis and Hodges (2013) and Hersh (2013b), who found that people with deafblindness often perceive the white cane as stigmatizing. The discussion among the participants showed the importance of finding one's own way to approach controversial accessibility aids.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, older participants who had frequently used the cane revealed only positive experiences. The ambivalence concerning the cane has previously been reported by Ellis and Hodges (2013) and Hersh (2013b), who found that people with deafblindness often perceive the white cane as stigmatizing. The discussion among the participants showed the importance of finding one's own way to approach controversial accessibility aids.…”
Section: Discussionmentioning
confidence: 69%
“…People who become deafblind have been described in terms of interactional powerlessness, vulnerability and struggling hard to adapt in a world that is sometimes perceived as hostile (Schneider, 2006). Stigmatization has been reported in relation to the use of mobility and communication aids (Hersh, 2013b). The situation of persons with deafblindness has also been referred to as a constant ontological insecurity (Danermark & Möller, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence also tells us that deafblindness is linked to poorer psychosocial well-being. Deafblindness is linked to a high prevalence of social isolation and loneliness,15 increased psychological distress,16 depression,15 17 vulnerability,18 perceived stigma19 and perceived inadequate support 1516 Therefore, psychosocial well-being may represent an important factor to consider in the HRQOL of people deafblindness.…”
Section: Introductionmentioning
confidence: 99%
“…Assistive devices, which are interchangeable with "assistive technology" and "adaptive equipment," are defined as any item purchased commercially or customized that improves functional abilities of the disabled individuals (Foti & Koketsu, 2013). Low vision assistive devices (LVADs) are used to enhance engagement in daily occupations and examples of LVADs include: electronic vision-enhancement system, prisms, lighting, filters, adaptive computer technology, audio players, recorders, notetakers, communication devices, optical devices, non optical aids, and mobility devices (Copolillo & Teitelman, 2005;Fok, Polgar, Shaw, & Jutai, 2011;Hersh, 2013). Optical devices, such as telescopic lenses and hand-held magnifiers, are particularly helpful for reading (Fok et al, 2011).…”
Section: Low Vision Assistive Devicesmentioning
confidence: 99%
“…Many assistive devices such as long canes or guide dogs may help promote independence in older adults with low vision. Despite the accessibility of long canes, which is a more traditional assistive device, long canes can be abandoned over time due to lack of proper training or inconvenience (Hersh, 2013;Whitmarsh, 2005). To maintain independence in community mobility, an alternative solution is to obtain a guide dog from organizations such as Guide Dogs for the Blind (GDB).…”
mentioning
confidence: 99%